Design and Implementation of a Digital Environmental Monitoring System. - Nuwagaba, Alfred (Kabale University, 2023)
In this report, an embedded digital environmental monitoring system, a solution for tracking environmental conditions at a remote location is presented. The environmental conditions at a particular location are measured using sensors and the results are transmitted to a mobile user on a global system for mobile communications (GSM) platform. Given that GSM based technology is widely spread across the world, has quality channeling and signaling, this makes it a preferred option for use in this project in comparison to other wireless technologies. This project focusses on the development of a simple and low-cost system based on embedded and GSM wireless technology. This system focused on the following environmental parameters of temperature, humidity, light intensity and rain to digitally. The detected parameters are then displayed on a liquid crystal display (LCD) and sent to a remote user through short message service (SMS). This digital environmental monitoring system can be used to remotely monitor different environmental conditions of a location.